Implementasi STEAM Pada Kegiatan Proyek Pembuatan Lampu Lalu lintas Untuk Anak Usia 5-6 Tahun - Delia Nurlina; Dindin Abdul Muiz Lidinilah; Qonita Qonita (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
The STEAM (Science, Technology, Engineering, Art, and Mathematics) approach is an educational innovation that offers early childhood learners experiences through activities integrating various disciplines. However, the implementation of STEAM elements within project-based activities relevant to children's daily lives requires further in-depth study. This research aims to describe the implementation of STEAM in a traffic light construction project for children aged 5–6 years. A descriptive qualitative approach was employed at TK PGRI Rancabogo. The subjects were children in "Group B" (aged 5–6) participating in the STEAM-based traffic light project. Data were collected through observation, interviews, and documentation, then analyzed using data reduction, data presentation, and conclusion-drawing techniques. The results indicate that the traffic light project successfully integrated the five STEAM elements. The Science element was evident when children observed whether the lights illuminated after assembly. The Technology element was demonstrated through the use of simple tools and materials. The Art element was visible in activities involving decoration and color selection, while the Mathematics element appeared as children recognized geometric shapes, counted the lights, and sequenced colors. Thus, this project serves as a viable alternative for implementing STEAM in early childhood education